LITERASI KEUANGAN DAN PERILAKU KEUANGAN SYARIAH MAHASISWA UM.PALOPO: MEDIASI FINANCIAL TECHNOLOGI DAN PERSONAL FINANCE - Firlianti; Rafika Akib; Siti Nur Ariska; Jumawan Jasman (FEB Universitas Sam Ratulangi Manado, 2023)
Abstrak Students organizing and managing their finances is something that is very important. Because after graduating from college they will enter the world of work. Poor financial behavior will reduce one's level of success in life. The economy at the student level has a major impact on the process of managing personal finances. Therefore, it is important to manage finances so that we can meet additional needs without disrupting personal and family finances. Even with all the sophistication of technology, it can also interfere with us in the process of managing finances at this time. This study aims to find out how students think in managing their finances with their understanding and knowledge. The sample used was non-probability sampling. In this study, we used a questionnaire which was distributed online to students and 160 respondents were sampled. And testing the hypothesis using the path analysis technique. The results of the study found that financial technology has a direct effect on Islamic financial behavior, financial literacy has a significant direct effect on financial technology, personal finance has a direct effect on Islamic financial behavior, while financial literacy has no direct effect on personal finance. Keywords: financial literacy, financial technology, personal finance, Islamic financial behavior